Layered LiNi1/3Mn1/3Co1/3O2 (NMC) with Optimized Morphology for Li-Ion Batteries. (26th November 2018) - Zukalova, Marketa; Prochazka, Jan; Pitna Laskova, Barbora; Zukal, Arnost; Kavan, Ladislav
Abstract : Commercial LiNi1/3 Mn1/3 Co1/3 O2 material is treated in appropriate way to provide cathode material with reasonable charge capacity and high cycling stability upon different charging/discharging rates. Electrochemical performance of the tested materials is studied by cyclic voltammetry of Li insertion and galvanostatic chronopotentiometry. An influence of calcination, surface area and particle size uniformity on the charge capacity and cycling stability is evaluated and the parameters of the optimized samples providing charge capacity of 141 mAh/g (cyclic voltammetry) and 144 and 135 mAh/g (galvanostatic chronopotentiometry) at 1 and 10C, respectively, represent a platform for scale up during the next period of the research.